Peran Jaksa Dalam Penanganan Tindak Pidana Korupsi Di Kejaksaan Negeri Sorong - Kambu, Yuliana Debora; Hidaya, Wahab Aznul (Journal of Law Justice (JLJ), 2023)
This study aims to explain the role and constraints faced by the prosecutor's office in handling corruption at the Sorong District Attorney's Office. The research method used in this study is an empirical research method using a legal sociology approach, the research specifications used are descriptive analysis, data processing is done through data collection techniques, namely primary data collection, namely observation and interviews and secondary data collection, namely documentation in the office. Sorong State Prosecutor's Office for Special Crimes. The results of the study show that the role of the Sorong State Attorney's Office in handling corruption crimes is handling corruption crimes by the Attorney General's Office through a series of investigations, investigations, and prosecutions. The obstacle is the unavailability of the State Attorney's Office and concrete evidence of the amount of state financial losses by non-Attorney institutions, namely the Supreme Audit Agency (BPK-RI), in this case the Supreme Audit Agency (BPK). BPK-RI). West Papua Province Representative in Manokwari.